A study of the nucleus-nucleus total reaction cross section of stable systems at intermediate energies: An application to 12C. (July 2018) - Hu, Liyuan; Song, Yushou; Hou, Yingwei; Liu, Huilan; Li, Hui
Abstract: A semi-microscopic analytical expression of the nucleus-nucleus total reaction cross section ( σ R ) was proposed based on the strong absorption model. It is suitable for stable nuclei at intermediate energies. The matter density distributions of nuclei and the nucleon-nucleon total cross section were both considered. Particularly, the Fermi motion effect of the nucleons in a nucleus was also taken into account. The parametrization of σ R was applied to the colliding systems including 12 C. The experimental data at energies from 30 to 1000 MeV/nucleon were well reproduced, according to which an approach of deriving σ R without adjustable parameters was developed. The necessity of considering the Fermi motion effect in the parametrization was discussed. Abstract : Highlights: A parametrization of the nuclear total reaction cross section was proposed. Nuclear density and cross sections between nucleons were considered. The Fermi motion effect of nucleons in a nucleus was included. The cross sections of 12C-involved collisions were expressed analytically.